Progressive skin fibrosis is associated with a decline in lung function and worse survival in patients with diffuse cutaneous systemic sclerosis in the European Scleroderma Trials and Research (EUSTAR) cohort - Wu, Wanlong; Jordan, Suzana; Graf, Nicole; Pena, Janethe De Oliveira; Curram, John; Allanore, Yannick; Matucci-Cerinic, Marco; Pope, Janet E.; Denton, Christopher P.; Khanna, Dinesh; Distler, Oliver; Matucci-Cerinic, Marco; et al. (Annals of the Rheumatic Diseases, 2019)
Objectives To determine whether progressive skin fibrosis is associated with visceral organ progression and mortality during follow-up in patients with diffuse cutaneous systemic sclerosis (dcSSc).
CRIS-Team WoS Importer:2019-06-25